Student Perspectives of Academic Integrity in an Online Environment: A Pilot Study - Richards, Rhonda (Archives of Business Research, 2021)
The March 2020 COVID-19 pandemic caused many universities to move face-to-face and hybrid courses to completely online formats, resulting in increased challenges to academic integrity. Although academic misconduct and academic dishonesty among students is nothing new, the literature is inconclusive as to whether there is more cheating in online classes than in face-to-face classes. However, online education has made it much more difficult for instructors to detect instances of cheating. The purpose of this study is to identify student perceptions and attitudes regarding violations of academic integrity, particularly in online courses. An Internet survey link was sent to all students enrolled at a southwestern university.